A Novel Bacteriocin From Lactobacillus Pentosus ZFM94 and Its Antibacterial Mode of Action - Dai, Mengdi; Li, Yanran; Xu, Luyao; Wu, Danli; Zhou, Qingqing; Li, Ping; Gu, Qing (Frontiers in Nutrition, 2021)
Bacteriocins are bioactive antimicrobial peptides synthesized in the ribosome of numerous bacteria and released extracellularly. Pentocin ZFM94 produced by Lactobacillus pentosus ZFM94, isolated from infant feces with strong antibacterial activity, was purified by ammonium sulfate precipitation, dextran gel chromatography and reverse-phase high performance liquid chromatography (RP-HPLC). The molecular mass of the purified bacteriocin was 3547.74 Da determined by Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS). Pentocin ZFM94 exhibited broad-spectrum antimicrobial activity against tested Gram-positive and Gram-negative bacteria, and the minimal inhibitory concentrations (MICs) of Micrococcus luteus 10209, Staphylococcus aureus D48 and Escherichia coli DH5α were 1.75 μM, 2.00 μM and 2.50 μM, respectively. Pentocin ZFM94 was heat-stable (30 min at 80 ℃) and showed inhibitory activity over a wide pH range (5.007.00). It could be degraded by trypsin and pepsin, but not by amylase, lysozyme, lipase and ribonuclease A. Fluorescence leakage assay showed that pentocin ZFM94 induced cell membrane disruption and caused leakage of cellular content. Furthermore, lipid II was not an antibacterial target of pentocin ZFM94. This study laid the foundation for further development and utilization of Lactobacillus pentosus ZFM94 and its bacteriocin.